2012
DOI: 10.1097/crd.0b013e318247cd15
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Carotid Artery Dissection

Abstract: Carotid artery dissection is a cause of stroke, especially in young and middle-aged patients. A dissection occurs when there is an intimal tear or rupture of the vasa vasorum, leading to an intramural hematoma, which is thought to result from trauma or can occur spontaneously, and is likely multifactorial, involving environmental and intrinsic factors. The clinical diagnosis of carotid artery dissection can be challenging, with common presentations including pain, partial Horner syndrome, cranial nerve palsies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(35 citation statements)
references
References 136 publications
(335 reference statements)
1
29
0
2
Order By: Relevance
“…There is one meta-analysis of retrospective cases in which patients had received thrombolysis after experiencing a CAD-related stroke [29]; this reported that 3.1% suffered SICH, and in these patients, mortality was 9.0%, which are similar rates as found in our meta-analysis and also in the European Cooperative Acute Stroke Study III studies and SITS-ISTR [27,31]. In addition, we found that patients with intracranial extension of dissection had a high SICH rate and mortality in a multicenter study [32], in agreement with the view of some clinicians, fearing that sub-adventitial dissections with intracranial extension especially in posterior circulation treated with tPA could cause bleeding into the adjacent tissue, resulting in SICH or subarachnoid hemorrhage [22,33,34]. However, 3 earlier studies indicated that thrombolysis was not any more likely to adversely affect patients with intracranial extension of dissection more than other patients [35,36,37].…”
Section: Discussionsupporting
confidence: 69%
“…There is one meta-analysis of retrospective cases in which patients had received thrombolysis after experiencing a CAD-related stroke [29]; this reported that 3.1% suffered SICH, and in these patients, mortality was 9.0%, which are similar rates as found in our meta-analysis and also in the European Cooperative Acute Stroke Study III studies and SITS-ISTR [27,31]. In addition, we found that patients with intracranial extension of dissection had a high SICH rate and mortality in a multicenter study [32], in agreement with the view of some clinicians, fearing that sub-adventitial dissections with intracranial extension especially in posterior circulation treated with tPA could cause bleeding into the adjacent tissue, resulting in SICH or subarachnoid hemorrhage [22,33,34]. However, 3 earlier studies indicated that thrombolysis was not any more likely to adversely affect patients with intracranial extension of dissection more than other patients [35,36,37].…”
Section: Discussionsupporting
confidence: 69%
“…brain injuries, fractures, etc.) [1, 6, 13, 14]. But it also has certain limits, especially during the diagnostic of critically injured patients in the trauma room.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many prospective observational studies, there remains much debate over the treatment choice in CAD [12,13,14,15,16,17,18]. Therefore, the decision to choose an antithrombotic agent and duration of treatment for CAD remains empiric and requires customizing to patient-specific risks and benefits.…”
Section: Discussionmentioning
confidence: 99%